The conception of the net weather station for measuring the microclimate of the forest - Paweł, Szymański; Marcin, Szymański; Michael, Smieja; Wojciech, Ożga; Brach, Michał (International Conference “Environmental Engineering”, 2017)
The project of meteorological station is designed to monitor the state of the weather on the selected (forest areas) as well as the colleting the data to analyze the dynamic of the changes weather parameters. The main idea presented in this paper, base on assumption that single weather station can be used as a part of net. The simultaneous and continuous measurement of many parameters such as temperature, pressure, humidity and sunlight located at grid points could work out finaly the weather map combined with the digital terrain model. The modern electronic make possible flexible connecting indywidual stations in subsytems and exchange of huge amount of inforamtion leading to build base knowledge. In the first part of the article it is presented the conception of the information system. In the next part there are outlined the results of works with the prototype of the measure mode. Dedicated to applications in forestry prototype of device, can be used to measure temperature, pressure, humidity and sunlight. The additional features of the device are the possibility of writing data on micro SD card, supplemented with current time, day, and year. The design and research is a pilot, before the creation of a regular grid of sample plots with the use of many such devices. The objective is to gather accurate meteorological data from the interior of the forestased geostatistical analysis, necessary for breeding purposes. Because of their design frames weather, it can be installed on most trees. Presented prototype of basic station used in the concept of measuring net, generates data from the sensors, which are strongly correlated with the compared professional station.